Analisis Lingkungan Ex Lokalisasi pada Kepribadian Peserta Didik SD Rahmat Surabaya - Putri Ramadhani, Anindya Maharani; Larasati, Diyas Age; Ismawati, Aprilia Dwi; Nafia, Zidna Ilma; Oktavia, Neyla Najwa; Nur Izzah, Amelia Endah (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyze the impact of the former localization environment on the personality development of students at Rahmat Elementary School, Surabaya. The social environment previously known as a localization area has the potential to have a negative influence on the formation of children's character, especially in aspects of behavior, emotions, and social interactions. The research method used was observation and interviews with students in grades IV and V. The results of the study showed that some students tended to be easily influenced by the environment, had difficulty controlling their emotions, lacked self-confidence, and showed signs of psychological stress. However, there were also students who had moral resilience and were able to maintain a positive attitude. The conclusion of this study emphasizes the importance of the role of schools, teachers, and parents in minimizing the negative impact of the environment and strengthening the formation of children's personalities positively.